2020
DOI: 10.1039/c9tc06469a
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the properties of SnO2nanocrystals: morphological effects on structural, photoluminescence, photocatalytic, electrochemical and gas sensing properties

Abstract: Tin dioxide (SnO2) is a material of ever increasing scientific attention as a result of its many constructive and varied physical properties: different morphological structures of SnO2 nanocrystals modulate the performance of diverse applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 298 publications
0
56
0
Order By: Relevance
“…Their observed bandgaps were estimated to be 3.1, 3.0, 2.9, and 3.1 eV for Method 1–Day 2, Method 2–Day 2, Method 3–Day 2, and Method 3–Day 7, respectively. It was reported that the narrower bandgaps compared to a well-known bandgap of 3.6 eV [ 2 , 25 ] is due to the elevation of the valence-band maximum of SnO 2 induced by the oxygen vacancies [ 22 , 26 ]. The bandgap of Method 1–Day 8 and Method 2–Day 7 was 3.6 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their observed bandgaps were estimated to be 3.1, 3.0, 2.9, and 3.1 eV for Method 1–Day 2, Method 2–Day 2, Method 3–Day 2, and Method 3–Day 7, respectively. It was reported that the narrower bandgaps compared to a well-known bandgap of 3.6 eV [ 2 , 25 ] is due to the elevation of the valence-band maximum of SnO 2 induced by the oxygen vacancies [ 22 , 26 ]. The bandgap of Method 1–Day 8 and Method 2–Day 7 was 3.6 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Over the last two decades, the synthesis of self-assembled tin oxide (SnO 2 ) semiconductor nanoparticles has been a fascinating research area because of their potential applications in gas sensing, lithium-ion batteries, solar cells, and catalysts for various organic reactions [ 1 ]. These versatile applications associated with their photophysical, chemical, and electronic properties can be realized by tuning certain factors, such as the size, shape, crystallinity, and electronic states of the SnO 2 nanoparticles [ 2 ]. In particular, self-assembled 3D SnO 2 nanoaggregates with high surface areas [ 3 , 4 ] have received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Broadening of the O-1s peak on the higher energy side indicates presence of oxygen deficient tin oxide. 42 From the XPS data, the ratio of O/Sn was calculated using the eqn. The TEM images for the NPs obtained via e-beam irradiation depicts self-assembling of the initially formed small spherical globules into larger sized ones, which further gets interconnected to form an entangled structure (fig.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…Strongly thermally stable in the air up to 500°C 9 , Tin has two types of oxides; stannous oxide (SnOromarchite) and stannic oxide (SnO 2 cassiterite) 10 . Tin oxide (SnO 2 ) is one of the (n-type) metallic semiconductors that has a wide gap (3.6ev) in room temperature, and its excellent properties make it a suitable material for many applications, in transparent electrodes, solar cells, gas-sensing photocatalysts, photoelectric devices 11,12 One of the influences that affect the performance of the sensors is the increase in the surface area , as attention has been paid to preparing crystalline materials with a large surface area where the properties of crystalline materials are very sensitive on the surface of atomic structures, especially applications such as solar cells and gas sensors [13][14][15] . Oxide nanoparticles can be prepared by both Physical and Chemical methods.…”
Section: Introductionmentioning
confidence: 99%